The role of strategic management accounting and its impact on the competitive advantage in Jordanian industrial companies - كناكرية رائد محمد (Journal of Economics and Administrative Sciences, 2020)
This study aimed to recognize and understand the concept of strategic management accounting (SMA) and how it’s the effect on the competitive advantage for industrial companies in Jordan. The study’s importance arises due to the lack of Arab studies that dealt with this topic, in addition to the important and vital role of strategic management accounting on companies that represent the artery of the decision-making process, and to identify the benefits associated with SMA technology. The necessary data were collected through the literature review and theoretical study of the references that relevant to the study subject, in addition to a questionnaire developed for this purpose, the study used (124) out of (250) questionnaires that were distributed to the higher departments in the industrial companies in Jordan. Plus, to achieve the study goals, the SPSS statistical program was used to analyze data and to discover the nature of the impact. The mean and standard deviations were calculated, in addition to the regression and correlation test to elaborate on the natural relation between study variables that were analyzed. The concept of strategic management accounting was measured by (the concept of strategic cost, the concept of nine The strategic t and the concept of the brand) and the competitive advantage was measured through (achieved profits, product quality, customer satisfaction, product development, and market share). The study concluded that companies in Jordan practice this concept, furthermore the result indicated that there is a statistically significant effect of the SMA concept on competitive advantage. The study also concluded that SMA techniques is not a complete alternative for traditional accounting managerial, but it is also complementary to it. The study also recommended that companies are required to set long-term strategic goals due to their impact on competition and environmental changes. The study also concluded that the SMA differs in its comparison with the practice of managerial accounting and was adopted by industrial companies in Jordan as a principle of operation and not as a theoretical concept.